Celebrating Bird : The Triumph of Charlie Parker - Giddins, Gary (Book collections on Project MUSE., 2013)
"Within days of Charlie "Bird" Parker's death at the age of thirty-four, a scrawled legend began appearing on walls around New York City: Bird Lives. Gone was one of the most outstanding jazz musicians of any era, the troubled genius who brought modernism to jazz and became a defining cultural force for musicians, writers, and artists of every stripe. Arguably the most significant musician in the country at the time of his death, Parker set the standard many musicians strove to reach--though he never enjoyed the same popular success that greeted many of his imitators. Today, the power of Parker's inventions resonates undiminished; and his influence continues to expand. Celebrating Bird is the groundbreaking and award-winning account of the life and legend of Charlie Parker from renowned biographer and critic Gary Giddins, whom Esquire called "the best jazz writer in America today." Richly illustrated and drawing primarily from original sources, Giddins overturns many of the myths that have grown up around Parker. He cuts a fascinating portrait of the period, from Parker's apprentice days in the 1930s in his hometown of Kansas City to the often difficult years playing clubs in New York and Los Angeles, and reveals how Parker came to embody not only musical innovation and brilliance but the rage and exhilaration of an entire generation. Fully revised and with a new introduction by the author, Celebrating Bird is a classic of jazz writing that the Village Voice heralded as "a celebration of the highest order"--A portrayal of a jazz virtuoso whose gargantuan talent was haunted by his excesses and a view into the ravishing art of one of jazz's most commanding and remarkable figures."--